PENATAAN POTENSI KAWASAN WISATA BAHARI DI DESA OLELE - Hasanah, Luluk Lailatul; Eka, Rahmawati (RADIAL : Jurnal Peradaban Sains, Rekayasa dan Teknologi, 2023)
Olele is one of the villages in the Sulawesi archipelago with excellent potential as a tourist spot. The village, which is located in Gorontalo, is nicknamed "The Hidden Paradise in Sulawesi“ because of its stunning underwater beauty. The aim of the research is to rearrange the marine tourism area in Olele Village and optimally add building functions to improve the tourist area. The method used is descriptive qualitative method, the research location is in Olele Village with the optimal rearrangement of existing buildings and the addition of building functions, with survey and interview research types.The results of this study are (1) the concept of structuring the marine tourism area (2) the optimal addition of building functions for the previous building. The conclusion from the research conducted is that there are differences in the layout of the building from the old building in addition to creating an optimal building function to improve the tourist area. The results of the research will be material for corrections for the local government. For the benefit of building design it is necessary to criticize k architecture from architects together with the community, so that discussions and inputs are given to pay more attention to the condition of the marine tourism area site.